A Human-Mouse Hybrid HLA-A2-IG Dimer Inhibits the Proliferation of CD4+T Cells In Vitro - Jeza, Victor Tunje; Jun , Chen; Xiongwen , Wu (Multidisciplinary Journal of Technical University of Mombasa, 2020)
Currently, general immunosuppressive drugs are used to maintain tolerance to allografts. However, these drugs have a major drawback of rendering the patient susceptible to infections and other side effects like malignancy and drug related toxicities with an overall rejection of the organ at some point. Previous studies have shown that MHC-Ig dimers may suppress alloresponsive T cells in a donor specific manner in vitro. This work aimed to answer the question as to whether these dimers will surmount rejection through the direct mechanism of allorecognition by suppressing alloreactive CD8+ T cells. To do this, we first identified two mice models with a single mismatch at the MHC loci. We found and procured white albino NOD mice which happened to be transgenic for HLA-A2 and HLA-A24 molecules. We then constructed a human-mouse hybrid HLA-A2-Ig dimer by overlap-PCR to join parts of two different already cloned plasmids to form the full length HLA-A2β2α1α2murineα3 insert which was then cloned to pcDNA3.1 to form pcDNA3.1HLA-A2β2α1α2murineα3. The IgG2bFc region was added by restriction digestion and ligation to form the plasmid pcDNA3.1HLA-A2β2α1α2murineα3IgG2bFc. Sequencing was done and confirmed that the construction and cloning were successful. The plasmid pcDNA3.1HLA-A2β2α1α2murineα3IgG2bFc was then transfected by electroporation to J558L cells. Screening was done using G418 for 4 weeks in cell culture. We purified the dimer by affinity chromatography and then used ELISA to confirm expression of the dimer. The purified dimer was then used in 1-way MLC experiments where responder cells were mice cells expressing HLA-A24 molecules while stimulator cells were mice cells expressing HLA-A2 molecules. Cell samples were gated on anti-mouse CD3-PE/CY7, anti-mouse CD4-PE, and anti-mouse CD8-APC/CY7. Cell proliferation was analysed using CFSE. Our results showed that the proliferation of CD4+ T cells was inhibited in the presence of the dimer. This work is crucial for subsequent studies aiming to search for induction of donor specific tolerance.